Disentangling digesta passage rate in the gastrointestinal tract of male and female growing goats fed varying feeding levels using multivariate and metanalytical approaches: Inferring growth, sex, and intake effects on goats’ digesta passage rate - Gindri, M. [UNESP]; Moraes, L. E.; Teixeira, I. A.M.A. [UNESP] (Elsevier, 2021)
Digesta passage rate (kp) in ruminants is a very dynamic and complex process and is related to digestion, methane emission, and microbial growth. The objectives of this study were to identify variables related to kp in gastrointestinal tract (GIT) segments by creating latent variables using multivariate factor analysis and access the important sources of variation (i.e., goats’ growth, sex, or feeding levels) of each created latent variables. Two data set were used from three studies with Saanen goats. Data set Growth was composed of individual records of castrated males (n = 36), females (n=34), and intact males (n=33) fed ad libitum and slaughtered at 15 (16.62 ± 0.96 kg body weight (BW)), 22 (23.09 ± 1.33 kg BW), 30 (30.67 ± 2.25 kg BW), 37 (38.02 ± 1.61 kg BW), or 45 (44.12 ± 1.95 kg BW) kg BW. Data set Feeding Level was composed of individual records of castrated males (n=38), females (n=33), and intact males (n=36) fed ad libitum (26.82 ± 2.54 g/kg BW), 75% (22.90 ± 1.99 g/kg BW) or 50% (20.44 ± 2.05 g/kg BW) of ad libitum, over 109 ± 10 days. Four orthogonal latent variables were extracted from each data set, and they explained around 61% of the original variability of each data set. Digesta passage rate had different responses whether evaluated in growing goats or goats fed varying feeding levels in the long term. Growing goats had kp of solutes in reticulorumen, omasum, and colon-rectum positively related to DM intake level and chews/kg DM intake and negatively related to GIT sections capacity and BW growth. Moreover, DM intake level, reticulorumen kp of particles, and large intestine kp of solutes and particles were all positively related in growing goats. Goats fed varying feeding levels had kp of solutes in all GIT segments positively related to feeding level and capacity of GIT segments and negatively related to chews/kg DM intake. Reticulorumen kp of particles was not associated with any of the selected factors of the data set Feeding Level. In conclusion, DM intake level is the driving force of GIT kp of solutes in growing goats and goats fed varying feeding levels in the long term. Also, the GIT kp of solutes is negatively affected by GIT capacity and positively affected by chews/kg DM intake only in growing goats. Moreover, kp of particles in reticulorumen and kp of particles and solutes in large intestine of growing goats are positively related among them and positively related to DM intake level. However, reticulorumen kp of particles is constant in goats fed varying feeding levels in the long term. Sex effect on GIT kp seemed to depend on chews/kg DM intake, however, further investigations are needed to fully understand sex effects on kp.
Keywords: Digesta kinetic; Feed intake; Gut; Pool size; Saanen